Decitabine Induced Delayed Cardiomyopathy in Hematologic Malignancy - Pradyumna Agasthi; Hemalatha Narayanasamy; Dan Sorajja; James Slack; Farouk Mookadam (Case Reports in Cardiology)
Decitabine is a pyrimidine analogue of nucleoside cytidine, used for the treatment of myelodysplastic syndromes, chronic myelogenous leukemia, and acute myelogenous leukemia. We present a case of cardiomyopathy associated with decitabine used for secondary acute myelogenous leukemia. The patient presented with new heart failure symptoms and an ejection fraction decline.